2014
DOI: 10.1097/dcr.0b013e3182a84eba
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Criteria Underestimate Complete Pathological Response in Rectal Cancer Treated With Neoadjuvant Chemoradiotherapy

Abstract: The majority of patients attaining ypT0 status do not display mucosal features of complete response. When present, a mucosal complete response is statistically associated with ypT0 status, but is poorly sensitive. If rectal conservation after chemoradiation is to be pursued, alternative means of restaging are required to maximize the number who might benefit from this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 14 publications
5
107
2
1
Order By: Relevance
“…If an ulceration, palpable node or stenosis are found during examination, it means incomplete clinical response. 12 Two different terms …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If an ulceration, palpable node or stenosis are found during examination, it means incomplete clinical response. 12 Two different terms …”
Section: Discussionmentioning
confidence: 99%
“…But on the other hand, without surgery we can not reliably assess pCR as accuracy of other methods for assesment of tumour response to preoperative treatment is low. 12 Is there any possibility to assess preoperatively, whether patients responded to treatment completely and all tumor cells were destroyed? Clinical complete response (cCR) represents a list of clinical and endoscopic characteristics: whitening of rectal wall mucosa, telangiectasias within mucosa, scars in rectal wall, seen as light stiffness of the wall during the insuflation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent retrospective study demonstrated that most patients who demonstrate a pCR on microscopic evaluation do not display mucosal features indicative of a complete response on macroscopic examination. Clinical examination alone had a sensitivity of 26% specificity of 96% in predicting pCR [20].…”
Section: Complete Clinical Responsementioning
confidence: 99%